Clinico-pathological associations of serum VCAM-1 and ICAM-1 levels in patients with lupus nephritis - Yu, Kelvin YC; Yung, Susan; Chau, Mel KM; Tang, Colin SO; Yap, Desmond YH; Tang, Alexander HN; Ying, Shirley KY; Lee, Cheuk Kwong; Chan, Tak Mao (Lupus, 2021)
Objective We investigated the clinico-pathological associations of serum VCAM-1 and ICAM-1 levels in patients with biopsy-proven Class III/IV±V lupus nephritis (LN). Methods Serum VCAM-1 and ICAM-1 levels were determined by ELISAs. Sera from patients with non-renal SLE or non-lupus chronic kidney disease (CKD), and healthy subjects served as controls. Results Seropositivity rate for VCAM-1 and ICAM-1 was 93.10% and 37.93% respectively at the time of nephritic flare, and 44.83% and 13.79% respectively at remission, with both showing higher levels during flare (P < 0.05, for both). VCAM-1 level correlated with proteinuria, serum creatinine, and anti-dsDNA antibodies, and inversely correlated with C3. VCAM-1 level also correlated with leukocyte infiltration and fibrinoid necrosis/karyorrhexis scores in active LN kidney biopsies. ICAM-1 level correlated with proteinuria, but not anti-dsDNA or C3, nor histopathological features. VCAM-1 level increased 4.5 months before renal flare, while ICAM-1 increase coincided with flare, and both decreased after treatment. ROC analysis showed that VCAM-1 distinguished active LN from healthy subjects, LN in remission, active non-renal lupus, and CKD (ROC AUC of 0.98, 0.86, 0.93 and 0.90 respectively). VCAM-1 level in combination with either proteinuria or C3 was superior in distinguishing active LN from remission compared to the measurement of individual markers. Serum ICAM-1 level distinguished active LN from healthy subjects and LN patients in remission (ROC AUC of 0.75 and 0.66 respectively), but did not distinguish between renal versus non-renal lupus. ICAM-1 level in combination with markers of endothelial cell activation (syndecan-1, hyaluronan and thrombomodulin) was superior to proteinuria, anti-dsDNA, or C3 in distinguishing active LN from quiescent disease. Conclusion Our findings suggest potential utility of serum VCAM-1 and ICAM-1 in clinical management. Monitoring VCAM-1 may facilitate early diagnosis of flare. Combining selected biomarkers may be advantageous in diagnosing active LN. VCAM-1 may have a pathogenic role in renal parenchymal inflammation in active LN.